Komunikasi Profetik sebagai Paradigma Sistem Komunikasi Islam Kontemporer: Integrasi Nilai Kenabian dalam Komunikasi Digital - Ahmad Zein Daulay; Mohd Rafiq (Jurnal Pendidikan dan Dakwah, 2026)
The development of digital technology has brought about a significant transformation in contemporary communication systems, creating various ethical, social, and spiritual challenges for Islamic communication practices. This study employs a qualitative approach using library research to examine prophetic communication as a paradigm of the Islamic communication system in the digital era. Research data were collected from various scholarly sources, including books, journal articles, and relevant academic documents, and were analyzed using content analysis techniques through data reduction, interpretation, and synthesis. The findings reveal that prophetic communication is conceptually grounded in three fundamental pillars: humanization, liberation, and transcendence, which serve as the foundation of a contemporary Islamic communication system. The study further demonstrates that the integration of prophetic values with the prophetic attributes of ṣiddīq (truthfulness), amānah (trustworthiness), tablīgh (effective message delivery), and faṭānah (wisdom and intelligence) can establish an ethical, humanistic, and transformative model of digital communication. Moreover, prophetic communication has proven relevant in addressing various challenges of digital communication, including disinformation, hate speech, social polarization, and the commodification of religion in digital spaces. The analysis indicates that prophetic communication functions not only as an ethical framework for communication but also as a comprehensive paradigm of Islamic communication capable of integrating moral, social, and spiritual dimensions into modern communication practices. These findings underscore the importance of revitalizing prophetic values in building a civilized digital communication ecosystem. Therefore, prophetic communication can be positioned as a relevant, adaptive, and applicable paradigm of contemporary Islamic communication systems in responding to the challenges of the digital age. Perkembangan teknologi digital telah menciptakan transformasi besar dalam sistem komunikasi masyarakat yang menghadirkan berbagai tantangan etis, sosial, dan spiritual bagi praktik komunikasi Islam kontemporer. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research) untuk mengkaji komunikasi profetik sebagai paradigma sistem komunikasi Islam di era digital. Data penelitian diperoleh dari berbagai sumber pustaka berupa buku, artikel jurnal ilmiah, dan dokumen akademik yang relevan, kemudian dianalisis menggunakan teknik content analysis melalui proses reduksi, interpretasi, dan sintesis data. Hasil penelitian menunjukkan bahwa komunikasi profetik memiliki landasan konseptual yang dibangun atas tiga pilar utama, yaitu humanisasi, liberasi, dan transendensi sebagai fondasi sistem komunikasi Islam kontemporer. Penelitian ini juga menemukan bahwa integrasi nilai-nilai profetik dengan sifat kenabian berupa ṣiddīq, amanah, tablīgh, dan faṭānah mampu membentuk model komunikasi digital yang etis, humanis, dan transformatif. Selain itu, komunikasi profetik terbukti relevan dalam menjawab berbagai persoalan komunikasi digital seperti disinformasi, ujaran kebencian, polarisasi sosial, dan komodifikasi agama di ruang digital. Analisis penelitian menunjukkan bahwa komunikasi profetik tidak hanya berfungsi sebagai kerangka etika komunikasi, tetapi juga sebagai paradigma sistem komunikasi Islam yang mampu mengintegrasikan dimensi moral, sosial, dan spiritual dalam praktik komunikasi modern. Temuan ini menegaskan pentingnya revitalisasi nilai-nilai kenabian dalam membangun ekosistem komunikasi digital yang berkeadaban. Dengan demikian, komunikasi profetik dapat diposisikan sebagai paradigma sistem komunikasi Islam kontemporer yang relevan, adaptif, dan aplikatif dalam menghadapi tantangan era digital.